2013
DOI: 10.3109/13880209.2013.782505
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase, hyaluronidase and elastase inhibitory potential of standardized extract ofCentella asiatica

Abstract: Context: Centella asiatica (L.) Urban (Apiaceae), a valuable herb described in Ayurveda, is used in the indigenous system of medicine as a tonic to treat skin diseases. Objective: Centella asiatica methanol extract and its ethyl acetate, n-butanol and aqueous fraction, were subjected for the evaluation of skin care potential through the in vitro hyaluronidase, elastase and matrix metalloproteinase-1 (MMP-1) inhibitory assay. Materials and methods: The C. asiatica plant was extracted with methanol and fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
(22 reference statements)
1
30
0
3
Order By: Relevance
“…This is probably closely related to biologically active compounds that have been extracted from the plant. The methanol extracts of this plant showed greater inhibition activity of the analyzed enzymes than aqueous extracts [ 74 , 78 ]. As part of this work, water-glycerin extracts were analyzed, which, compared to analyses carried out by other authors, showed greater inhibition capacity than aqueous extracts, but worse than ethanol extracts.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably closely related to biologically active compounds that have been extracted from the plant. The methanol extracts of this plant showed greater inhibition activity of the analyzed enzymes than aqueous extracts [ 74 , 78 ]. As part of this work, water-glycerin extracts were analyzed, which, compared to analyses carried out by other authors, showed greater inhibition capacity than aqueous extracts, but worse than ethanol extracts.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a decrease in skin elasticity and premature skin aging was significantly correlated with an increase in elastase and hyaluronidase. Therefore, one mechanism to inhibit aging was to reduce various enzyme activities that support matrix degradation from the abundant connective tissues in the skin (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…HA skin effects could be limited by enzymatic degradation by hyaluronidase. 28 An interesting effect of CAE is that it can inhibit the enzymatic action of hyaluronidase: Nema et al 29 have demonstrated that CAE has potent elastase, matrix metalloproteinase and hyaluronidase inhibitory effects. The hydrating serum we have evaluated in this trial contains glycerin, HA and CEA.…”
Section: Discussionmentioning
confidence: 99%